Pengaruh Jam Kerja Terhadap Jam Absensi Dan Produktivitas Karyawan: Studi Kasus Salah Satu Karyawan PT. XYZ - Kukuh Yulianto; Dety Mulyanti (sekolah Tinggi Ilmu Ekonomi Dharma Putra Semarang, 2023)
Productivity is something that many companies want to achieve, which will later affect the company's output in the form of results obtained, one of which is company profit, productivity is an indicator of employee performance at PT. XYZ, measured by the number of results obtained from daily activities which will impact on work results which will later be used as billing equipment for work results to customers. Taking a sample of employees in the report generation unit, the result is that the more working hours that employees go through will affect productivity the following day, this is due to employee eye fatigue working on reports in front of a computer screen. The more hours worked with additional overtime hours, the productivity will decrease.